THE IMPACT OF ONLINE SALES AND QRIS ON UMKM INCOME WITH FINANCIAL LITERACY AS A MEDIATING VARIABLE: A STUDY OF CULINARY UMKMS IN MALANG CITY - Mubarok, Muhammad Aunul; Purnamasari, Puji Endah (Universitas Nusa Cendana, 2025)
This study aims to examine the impact of online sales and QRIS on the income of UMKMs in Malang City, with financial literacy as a mediating variable. The population of this study includes culinary UMKMs in Malang City, with a sample selected using random sampling from a total of 16,417 culinary UMKMs. The study used a quantitative approach and analyzed the data using PLS-SEM to evaluate the relationships between the variables. The findings indicate that both online sales and QRIS positively influence UMKM income, with financial literacy significantly mediating these relationships. The results suggest that integrating digital tools with financial literacy can enhance the financial performance of UMKMs. However, the study is limited to a specific sector in a single city, and future research could explore the long-term effects of digital tools on UMKM sustainability and evaluate additional factors influencing business performance in the digital economy. Keywords: Online Sales; QRIS; Financial Literacy